The study on the role of laparoscopy in the blunt abdominal trauma: a case series - Sahu, Rakesh Kumar; Chandrakar, Sandeep; Ratre, Rajendra; Agrawal, Sujan Narayan (International Surgery Journal, 2022)
The blunt trauma to the abdomen is the leading cause of mortality and morbidity in India and also worldwide. The young and productive age group are the main victims. The common causes of blunt injury to the abdomen are road traffic accidents, assault, fall from height and work-related injuries. Abdominal trauma is present in 7-10% of all trauma victims and in cases of severe trauma, it is often associated with orthopedic, thoracic or central nervous system injuries. Identification of serious intra-abdominal injuries is often challenging. Thus, a rapid and accurate diagnosis is mandatory. The diagnostic laparoscopy has gained widespread acceptance as a valuable tool for the diagnosis and management of patients with blunt abdominal trauma. When the imaging techniques fail to give the precise diagnosis, diagnostic laparoscopy is a viable alternative for the management of such trauma. This case series consisted of 22 patients admitted to our institute. All the patients underwent diagnostic laparoscopy. The blunt trauma managed by laparoscopy while 12 patients required conversion to exploratory laparotomy. It was observed that the most common organ injured was spleen in 10 patients (45.4%), liver in 9 patients (40.9%), mesenteric injury in 4 patients (18.1%) and small bowel injury in 3 patients (13.6%) respectively. Diagnostic and therapeutic laparoscopy is a preferred in hemodynamically stable patients, it reduces the hospital stay and postoperative complications. This case series underlines the importance of diagnostic and therapeutic application of laparoscopy in the victims of blunt injury abdomen.